Different Institutions and Different Values: Exploring First-Generation Student Fit at 2-Year Colleges - Tibbetts, Yoi; Priniski, Stacy J.; Hecht, Cameron A.; Borman, Geoffrey D.; Harackiewicz, Judith M. (Frontiers in Psychology, 2018)
First-generation college students (students for whom neither parent has a 4-year degree) face a number of challenges as they attempt to obtain a post-secondary degree. They are more likely to come from working-class backgrounds or poverty (Reardon, 2011)and attend lower quality high schools (Warburton, Bugarin, & Nunez, 2001) while not benefiting from the guidance of a parent who successfully navigated the path to higher education. First-generation college students also contend with belonging or “fitting in” concerns due a perceived mismatch between their own values and the values implicit in institutions of higher education (Stephens, Fryberg, Markus, Johnson, & Covarrubias, 2012). Specifically, prior research has demonstrated that first-generation college students face an unseen disadvantage that can be attributed to the fact that middle-class norms of independence reflected in American institutions of higher education can be experienced as threatening by many first-generation students who have been socialized with more interdependent values commonly espoused in working-class populations. The present research examines this theory (cultural mismatch theory) in the understudied context of two-year colleges and tests if a values-affirmation intervention (i.e., an intervention that has shown promise in addressing identity threats and belonging concerns) can be effective for first-generation college students at these two-year campuses. By considering the tenets of cultural mismatch theory in the creation of the values-affirmation interventions we were able to vary different aspects of the intervention in order to examine how its effectiveness may depend on the nature and magnitude of a perceived cultural mismatch. Results from surveying faculty and students at two-year colleges indicated that compared to traditional four-year institutions, the norms of two-year colleges and the motivations of first-generation students may be different. That is, first-generation student motives may be more consistent (and thus less mismatched) with the cultural context of two-year colleges which could result in fewer belonging concerns when compared to first-generation students at four-year institutions. This may carry implications for the efficacy of values-affirmation interventions and could help explicate why first-generation students in the current sample perceived a greater match with their college when they reflected on their interdependent values.